HUNIAN BERULANG SITUS GUA MACAN (TINJAUAN BERDASARKAN DATA ARKEOLOGI DAN GEOLOGI) - Nurani, Indah Asikin (BRIN, 1996)
The inhabitants of Macan Cave in their occupancy pattern are influenced by human factors and natural factors. The human factor is a factor that is carried out based on the demands of their life with the availability of the surrounding ecological potential. Meanwhile, natural factors are factors that do not involve human intervention at all and cannot be controlled by humans.